2001
DOI: 10.1046/j.1460-9568.2001.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenoreceptor‐mediated modulation of the spinal locomotor pattern during swimming in Xenopus laevis tadpoles

Abstract: This study focused on the contribution of different adrenoreceptor subtypes to the modulation of fictive swimming activity in a relatively simple, yet intact, lower vertebrate system, the immobilized Xenopus laevis tadpole and explored their possible role in mediating the noradrenergic modulation of spinal motor networks. In Xenopus embryos, near the time of hatching, activation of alpha(1) adrenoreceptors increased the duration of episodes of fictive swimming, whilst in larvae, 24 h after hatching, they were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 55 publications
5
27
0
Order By: Relevance
“…NA has three modulatory effects on fictive swimming: (1) it also slows swimming frequency by increasing glycinergic inhibition from commissural interneurons (McDearmid et al, 1997); (2) it can increase GABA release onto motor neurons, shortening swimming episode durations (McDearmid, 1998;Fischer et al, 2001); and (3) it can decrease the longitudinal delay of motor bursts along the body by enhancing postinhibitory rebound in motor neurons (Merrywest et al, 2003). NA mediates these three effects via the activation of ␣-adrenoreceptors (Fischer et al, 2001;Merrywest et al, 2002Merrywest et al, , 2003. Because of these similarities in both the effects on swimming and the underlying mechanisms, we used two pharmacological strategies to investigate the possible hierarchical relationship between NO and NA.…”
Section: Resultsmentioning
confidence: 99%
“…NA has three modulatory effects on fictive swimming: (1) it also slows swimming frequency by increasing glycinergic inhibition from commissural interneurons (McDearmid et al, 1997); (2) it can increase GABA release onto motor neurons, shortening swimming episode durations (McDearmid, 1998;Fischer et al, 2001); and (3) it can decrease the longitudinal delay of motor bursts along the body by enhancing postinhibitory rebound in motor neurons (Merrywest et al, 2003). NA mediates these three effects via the activation of ␣-adrenoreceptors (Fischer et al, 2001;Merrywest et al, 2002Merrywest et al, , 2003. Because of these similarities in both the effects on swimming and the underlying mechanisms, we used two pharmacological strategies to investigate the possible hierarchical relationship between NO and NA.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have emphasized the role of the NAergic system in motor rhythms and segmental reflex modulations in animal models and humans (as for examples: Kitazawa et al, 1985; Chau et al, 1998a; Jankowska et al, 1998; Kiehn et al, 1999; Remy-Neris et al, 1999; Sqalli-Houssaini and Cazalets, 2000; Fischer et al, 2001; Barbeau and Norman, 2003; Gabbay and Lev-Tov, 2004; Machacek and Hochman, 2006; Barriere et al, 2008). Our data shed light on the complexity of the cellular bases of the NAergic modulation in the motor spinal networks.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that noradrenergic modulation of the spinal swim‐pattern generator in Xenopus may be mediated via activation of α‐ and β‐adrenoreceptors. Both α 1 ‐ and α 2 ‐receptors modulate the frequency and duration of swimming, while α 1 ‐ and β‐receptors modulate longitudinal co‐ordination (Fischer et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%